SOCIAL MEDIA INTERDISCIPLINARY IN MULTIMODALITY OF INTERACTIVE ARTS AND CULTURE LEARNING FOR MILLENIALS - Yasinda Widya Fahmi; Djuli Djatiprambudi; Warih Handayaningrum (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to explore the problems in learning interactive art and culture at Junior High School level which was categorized as the millennial generation. The focus of this study laid in the interdisciplinary aspect of social media in multimodality of learning arts and culture. In order to reveal the opportunities and challenges of the use of social media in its development as a medium in interactive art and culture learning, as well as the students’ responses about it. This study used qualitative-analytic method. Data were obtained from observation conducted from January to June 2020 at junior high schools in Surabaya, East Java. The results showed that the learning involvement experienced by students had complexity and multimodality, including collaborative work, observing, and evaluating each other's work, and involvement in finding, identifying, and exploring trends related to delivery in social media as a medium for art and culture learning. This implied that this learning involvement was able to motivate students to be more actively involved in learning with a sense of joy; positioning artwork with others on social media; increasing the contextual and conceptual understanding in the learning materials and applying it as a process of actualizing aesthetic skills; and improving critical thinking and problem-solving skills.